PENINGKATAN PENGETAHUAN KADER POSYANDU DALAM PENILAIAN DAN INTERVENSI PERKEMBANGAN ANAK MENGGUNAKAN KARTU KEMBANG ANAK (KKA) - Elly Susilawati; Yanti Yanti; Findy Hindratni (Jurusan Kebidanan Poltekkes Kemenkes Riau, 2022)
Abstract Stunting occurs from the womb and is only seen when the child is 2 years old. The Child Flower Card (KKA) is a simple tool used to monitor children's development and intelligence as well as a tool to detect deviations or developmental disorders as early as possible that can be done by mothers or families of toddlers as well as Posyandu cadres and Toddler Family Development Cadres. The purpose of this community service activity is to increase the knowledge and ability of posyandu cadres in conducting developmental assessments and interventions using KKA. The activities will be carried out from February to July 2022, which is located in Pandau Jaya Village, Siak Hulu District, Kampar Regency. The target of community service is the cadres of Posyandu Pandau Jaya Village, totaling 31 participants from 16 Posyandu located in the working area of ​​Pandau Jaya Health Center. The method of implementing community service is carried out in the form of training for cadres in the form of material debriefing, demonstration of how to assess the development of infants under five, practice assessing developments in Posyandu and evaluation of implementation in the field. The training site is held at the village office and practical developmental assessment activities are held at the Posyandu. The results obtained were an increase in participants' knowledge, from an average score of 50 to an average of 85 through pretest and posttest. It is recommended to posyandu cadres in Pandau Jaya Village to routinely conduct developmental assessments and interventions for infants and toddlers using KKA on posyandu opening days and BKB. Keywords: Posyandu Cadre, Development, Child Flower Card